The Efficacy and Safety of Revefenacin for the Treatment of Chronic Obstructive Pulmonary Disease: A Systematic Review - Zhang, Jiaxing; Xie, Yihong; Kwong, Joey Sum-wing; Ge, Long; He, Rui; Zheng, Wenyi; Han, Jing; Zhang, Rui; Zhao, Huaye; He, Yuru; Li, Xiaosi (Frontiers in Pharmacology, 2021)
Background Revefenacin (REV) is a novel once-daily long-acting muscarinic antagonist (LAMA) in the treatment of moderate to very severe chronic obstructive pulmonary disease (COPD). This systematic review incorporating a dose-response meta-analysis aimed to assess the efficacy and safety of REV. Methods PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, VIP database, and Wanfang database were searched from their inception to April 2020. We included randomized controlled trials (RCTs) which evaluated the efficacy and safety of REV in COPD patients. Two reviewers independently performed study screening, data extraction, and risk of bias assessment. Outcomes consisted of the mean change in trough Forced Expiratory Volume in 1 second (FEV1) from baseline, adverse events (AEs), and serious adverse events (SAEs). A dose-response meta-analysis using the robust error meta-regression method was conducted. We used Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach to assess the quality of evidence. Results Nine RCTs (3,121 participants) were included in this systematic review. The meta-analyses indicatedLow-quality evidence demonstrated that 175 μg/day REV could significantly improve the trough FEV1 (MD=143.67, 95%CI: 129.67 to 157.68; I2=96%; 809 participants; studies=4; low quality) without increasing the risk of AEs (OR=0.98, 95%CI: 0.81 to 1.18; I2=34%; 2,286 participants; studies=7; low quality) or SAEs (OR=0.89, 95%CI: 0.55 to 1.46; I2=0%; 2,318 participants; studies=7; very low quality) compared to placebo. Furthermore, the effect of REV in increasing trough FEV1 was dose-dependent with an effective threshold of 88 μg/day (R2 = 0.7017). Nevertheless, only very low-quality to low-quality evidence showed that REV at a dose of 175 μg/day was inferior to tiotropium regarding the long-term efficacy, and its safety profile was not superior to tiotropium or ipratropium. Conclusion Current evidence shows that REV is a promising option for the treatment of moderate to very severe COPD. Due to most evidence graded as low quality, further studies are required to compare the efficacy, long-term safety and cost-effectiveness between REV and other LAMAs in different populations.